2007
DOI: 10.1016/j.biopsycho.2006.09.001
|View full text |Cite
|
Sign up to set email alerts
|

First evidence for differential and sequential efferent effects of stimulus relevance and goal conduciveness appraisal

Abstract: In the context of a memory task, participants were presented with pictures displaying biological and cultural threat stimuli or neutral stimuli (stimulus relevance manipulation) with superimposed symbols signaling monetary gains or losses (goal conduciveness manipulation). Results for heart rate and facial electromyogram show differential efferent effects of the respective appraisal outcomes and provide first evidence for sequential processing, as postulated by Scherer's component process model of emotion. Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 32 publications
8
65
1
Order By: Relevance
“…If NoGo trials are appraised as obstructive to the goal of responding, enhanced activity of the corrugator muscle should occur. Thus, Aue, Flykt, and Scherer (2007) have shown a signiWcant eVect of the goal conduciveness appraisal on corrugator activity as elicited by losing or winning events in a picture viewing paradigm.…”
Section: Predictionsmentioning
confidence: 95%
“…If NoGo trials are appraised as obstructive to the goal of responding, enhanced activity of the corrugator muscle should occur. Thus, Aue, Flykt, and Scherer (2007) have shown a signiWcant eVect of the goal conduciveness appraisal on corrugator activity as elicited by losing or winning events in a picture viewing paradigm.…”
Section: Predictionsmentioning
confidence: 95%
“…Thus, Aue et al (2007) showed that, as predicted by the CPM, the effect of stimulus relevance appeared earlier in the activity of both corrugator and zygomaticus than the effect of goal conduciveness appraisal. Lanctôt and Hess (2007) investigated the onset of movement in three facial muscles (corrugator supercilii, zygomaticus major, and orbicularis oculi) in response to appraisals of intrinsic pleasantness and goal conduciveness.…”
Section: The Sequential Hypothesis Of Appraisal Unfoldingmentioning
confidence: 96%
“…In these studies, researchers recorded the electromyography activity of two or more facial muscles (corrugator supercilii, brow region: frowning; zygomaticus major, cheek region: smiling; frontalis, forehead region: eyebrow raise) in different appraisal conditions. Aue, Flykt, and Scherer (2007) used visual stimuli that varied in relevance (biological threat vs. cultural threat vs. neutral) and manipulated their goal conduciveness (monetary gain vs. loss). Consistent with the idea of more difficulty in processing cultural threat, the stimuli belonging to this category were related to higher activation of the corrugator.…”
Section: Evidence For a Link Between Appraisals And Facial Expressionsmentioning
confidence: 99%
“…One such issue is whether appraisal variables are processed sequentially or in parallel. In Scherer's (2009) theory, appraisal variables can be processed in parallel but preliminary values for them are produced sequentially (Aue, Flykt, & Scherer, 2007;Grandjean & Scherer, 2008). Other appraisal theorists think the sequentiality assumption is overly restrictive.…”
Section: Type Of Processmentioning
confidence: 99%